PENGARUH ROTASI, MUTASI TERHADAP SEMANGAT KERJA DAN KINERJA PEGAWAI REKTORAT UNIVERSITAS RIAU - Amanda Olivia; Susi Hendriani; Yusni Hendriani (Jurnal Economica, 2019)
This study aims to determine the effect of rotation, mutations to work spirit and the performance of Riau University Rectorat employees. Analysis of the effect of data between research variables using 2-stage regression analysis. Regression analysis is used to examine and model the direction of relations between variables. One software that can be used is SPSS 23. The results of the study show that: (1), Rotation and mutation have a significant effect on the employee morale of the Riau University Rector's office. (2), Rotation has a significant effect on the employee morale of the Riau University Rector's office. (3), Mutations have a significant effect on the employee morale of the Riau University Rector's office. (4) The spirit of work has a significant effect on the performance of employees of the Riau University Rector's office.